Palladium(II) and Platinum(II) Complexes with Mixed Ligands of Tertiary Monophosphines and 5-Phenyl-1,3,4-oxadiazole-2-thione or 4,5-Diphenyl-1,2,4-triazole-3-thione - M. Qadir, Adnan; I. Abdullah, Ali; A. Al-Jibor, Subhi; A. K. Al-Allaf, Talal (Asian Journal of Chemistry, 2016)
Several new palladium(II) and platinum(II) complexes containing two types of ligands: tertiary monophosphines (L) and 5-phenyl-1,3,4-oxadiazole-2-thione ion (A) or 4,5-diphenyl-1,2,4-triazole-3-thione ion (B) have been prepared. The so obtained complexes trans-[PdA2L2], trans-[PdB2L2] and cis-[PtA2L2] were characterized by elemental analysis, IR, UV-Vis, 31P NMR spectroscopy, molar conductance and magnetic susceptibility measurements.